2019
DOI: 10.1038/s41598-019-47883-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of alkaline pH optimum of human glucokinase because of ATP-mediated bias correction in outcomes of enzyme assays

Abstract: Adenosine triphosphate (ATP) is a crucial substrate and energy source commonly used in enzyme reactions. However, we demonstrated that the addition of this acidic compound to enzyme assay buffers can serve as a source of unnoticed pH changes. Even relatively low concentrations of ATP (up to 5 mM) shifted pH of reaction mixtures to acidic values. For example, Tris buffer lost buffering capacity at pH 7.46 by adding ATP at a concentration higher than 2 mM. In addition to the buffering capacity, the pH shifts dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…This result is in reasonable agreement with previously reported literature for this ATP E-AB sensor on a 2 mm Au disk electrode . It was also observed that the peak shifted to a more positive potential with increasing ATP concentration (Figure a), which was attributed to a decrease in the solution pH. , …”
Section: Resultssupporting
confidence: 93%
“…This result is in reasonable agreement with previously reported literature for this ATP E-AB sensor on a 2 mm Au disk electrode . It was also observed that the peak shifted to a more positive potential with increasing ATP concentration (Figure a), which was attributed to a decrease in the solution pH. , …”
Section: Resultssupporting
confidence: 93%
“…The exact process leading to ATP hydrolysis remains unclear; still, much care has to be taken when analyzing environmental samples and drawing conclusions about activity (or biomass). Also, for all types of samples, the pH must be controlled with care, as it has been shown to affect the results ( Posimo et al, 2014 ; Šimèíková and Heneberg, 2019 ).…”
Section: Adenosine Triphosphate Assaysmentioning
confidence: 99%
“…This last experiment shows that the NBC increases intracellular buffering capacity by importing bicarbonate and this permits an increased lactate influx without decreasing intracellular pH. This evidence shows that the pHtome works in a coordinated manner [223].…”
Section: (C)mentioning
confidence: 58%
“…The optimum pH for glucokinase and hexokinase II was originally thought to be in the low alkaline level. However, it is now known to be more alkaline, in the range of 8.5–8.7 [ 224 ] for glucokinase. For other enzymes, their pH optimums are also alkaline, 7.8 for hexokinase I and 8.1 for hexokinase III [ 225 ].…”
Section: Discussionmentioning
confidence: 99%